Colorimetric chemosensor for detection of a volatile organic compound, ethylamine, under versatile conditions: Solution, thin-film, and dyed fabric - Noh, Ha Lim; Park, Young Ki; Oh, Byeong M.; Zheng, Jian; Kim, Sung Hoon; Lee, Woosung; Kim, Jong H. (Sensors and Actuators, B: Chemical, 2019)
In this this study, we present a new colorimetric chemosensor based on the isoindoline structure (ID1) for the detection of volatile organic compounds (VOCs), ethylamines. Spectral changes in the UV–vis absorption spectrum of ID1 were observed upon exposure to mono-ethylamine, resulting in significant and fast (<1.0 s) color changes detectable by the naked-eye. The reaction and kinetics of detection of different ethylamines (mono-, di-, and tri- ethylamines) by ID1 were investigated via 1H NMR and LC–MS characterization, binding stoichiometry, and association constant analyses, combined with density functional theory (DFT)-based quantum calculations. From these investigations, it was found that the mechanism of the detection is based on the nucleophilic attack, which was further evidenced by color change of ID1 when exposed to H2S likely due to the similar nucleophilicity to ethylamine. ID1 showed an efficient response to mono-ethylamine under versatile conditions, i.e., in the solution and solid (thin-films and dyed nylon fabric) states, which suggests applicability of ID1 to simple, effective, and practical sensors.
Keywords: Association constant; Chemo-sensors; Colorimetric chemosensor; Ethylamine; Isoindoline; Nucleophilic attack; Nucleophilicities; Quantum calculation; Colorimetric chemosensors; Density functional theory calculation; Ethylamine; Isoindoline; Volatile organic compounds (VOCs)